Rapid detection of Pseudomonad at species level by multiplex PCR in surgical units and ICU of Dhaka Medical College Hospital. (Bangladesh Journal of Medical Microbiology, 2016)
Pseudomonads are the most important gram negative organisms involved in various types of infection. This cross sectional study was conducted from January to December 2010 to isolate and identify Pseudomonad at species level in different clinical samples by culture and multiplex polymerase chain reaction (PCR) and to evaluate the efficacy of PCR in rapid detection of the bacteria at species level. Wound swab and tips of endotracheal tube were collected from hospitalized patients from different surgical units and intensive care unit (ICU) of Dhaka Medical College Hospital, Dhaka. Pseudomonads were isolated and identified at species level by culture, microscopy, different biochemical tests and PCR. Among 230 samples, 52.6% were surgical wound, 34.3% were burn wound and 9.6% were traumatic wound samples and 3.4% were tips of endotracheal tubes. Twenty six percent isolated organisms were Pseudomonas spp., 30.4% were Escherichia coli, and 13.5% were Staphylococcus aureus. Others were Proteus, Klebsiella pneumoniae, Acinetobacter baumannii and Enterobacter spp. In 19.67% samples mixed infections by other organism (Esch coli, Staph aureus, Proteus spp, Klebsiella spp) with Pseudomonas were detected and its distribution was highest in traumatic and burn wound. Multiplex PCR and different biochemical tests were used to identify 3 bacterial species of Pseudomonad. Among the species identified, 95.52% was Pseudomonas aeruginosa, 2.99% was Stenotrophomonas maltophilia and 1.49% was Burkholderia cepacia. The sensitivity of multiplex PCR was 95.08% and specificity 94.67%. PCR was the most rapid and more accurate method for detection of Pseudomonad at species level.Bangladesh J Med Microbiol 2016; 10 (2): 22-26